Use of static stiffness behaviour to characterise field hockey sticks - Covill, D.; Farr, J.; Katz, T.; White, D. (The Engineering of sport 7, Volume 2, 2008)
The aim of this paper was to quantify the static stiffness behaviour of a variety of field hockey sticks, and to move towards a Standard for their characterisation. A range of stick designs were tested at two different sections of the stick for bending stiffness. An Instron 8500 tensile and compressive testing apparatus was used to load the sticks in a simple 3-point bending regime and the results were independent of testing geometry. The mean flexural rigidity (EI product) of the samples ranged from 430-1069 Nm² towards the handle, and 310-636 Nm² towards the head and these were directly comparable to those measured in other studies of field hockey sticks. Small but acceptable variations (Standard deviation of 2%) were associated with the simplified compression adjustment factor, and these could be reduced further by minimising the compression at the point of load. The flexural rigidity for sticks of the same design were shown to vary considerably (up to 15% Standard deviation from the mean).